Developing entrepreneurial competence in emerging economies: co-creation, mutual learning, and immersion - Hastin Umi Anisah; Martaleni Martaleni; Muhammad Meidy Nur Hafidz (Journal of Innovation in Business and Economics, 2026)
The level of entrepreneurship in Indonesia remains relatively low despite its crucial role in driving economic growth and global competitiveness. One key constraint is the lack of direct exposure of students to real business practices, creating a gap between higher education and industry needs. This paper proposes the Co-creation, Mutual, and Immersive (CMI) Learning model as a structured framework to bridge this gap. Drawing on Service-Dominant Logic, Experiential Learning, Problem-Based Learning, and Constructivist theories, the model emphasizes collaborative engagement between students and entrepreneurs through knowledge sharing, joint problem-solving, and immersive business simulations. Our contributes to entrepreneurship education literature by addressing gaps in immersive learning applications in emerging economies and by offering a framework that integrates academic-industry collaboration for entrepreneurial ecosystem development.